1972
DOI: 10.1901/jeab.1972.18-481
|View full text |Cite
|
Sign up to set email alerts
|

THE DEVELOPMENT OF FIXED‐RATIO PERFORMANCE UNDER THE INFLUENCE OF RIBONUCLEIC ACID1

Abstract: The transition from fixed-ratio 1 performance (every response reinforced) to fixed-ratio 30 performance (every thirtieth response reinforced) was studied in nine pigeons. These were divided into three treatment groups given daily oral doses of saline, or 250 mg/kg/day or 500 mg/kg/day of yeast ribonucleic acid. Detailed computer-assisted analyses of how fixed-ratio behavior develops revealed the following typical sequence. After the transition, the first few ratios typically were emitted without long interresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

1975
1975
1989
1989

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Thus, Weiss and Gott (1972) found that the peaks of IRT distributions from pigeons on a FR 30 schedule sometimes shifted when subjects were administered amphetamines or other drugs. Furthermore, in several studies two or more peaks have been observed in IRT frequency distributions from FR schedules (Gott & Weiss, 1972;Mazur & Hyslop, 1982;Weiss & Gott, 1972). Gott and Weiss (1972), for example, found several peaks at multiples of about .3 sec, and they reported that the multiple peaks were the result of one or more ineffective pecks occurring between two recorded pecks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Weiss and Gott (1972) found that the peaks of IRT distributions from pigeons on a FR 30 schedule sometimes shifted when subjects were administered amphetamines or other drugs. Furthermore, in several studies two or more peaks have been observed in IRT frequency distributions from FR schedules (Gott & Weiss, 1972;Mazur & Hyslop, 1982;Weiss & Gott, 1972). Gott and Weiss (1972), for example, found several peaks at multiples of about .3 sec, and they reported that the multiple peaks were the result of one or more ineffective pecks occurring between two recorded pecks.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, in several studies two or more peaks have been observed in IRT frequency distributions from FR schedules (Gott & Weiss, 1972;Mazur & Hyslop, 1982;Weiss & Gott, 1972). Gott and Weiss (1972), for example, found several peaks at multiples of about .3 sec, and they reported that the multiple peaks were the result of one or more ineffective pecks occurring between two recorded pecks. Yet regardless of the shape of a particular IRT distribution, the results of Mazur and Hyslop (1982) and of the present study suggest that changing the ratio size or the type of ratio schedule will not substantially alter the shape of that distribution.…”
Section: Methodsmentioning
confidence: 99%
“…This is apparent from an experiment with pigeons trained on fixed-ratio schedules, in which recording the behavior in real time permitted a close examination of the acquisition process. Gott and Weiss (1972) traced the development of mature ratio performance in several different ways, beginning with the transition from continuous reinforcement to FR (fixed-ratio) 30. As Ferster and Skinner (1957) first demonstrated, the transition process is ragged.…”
Section: Spaced Respondingmentioning
confidence: 99%
“…Second, the proportion of very short IRTs increased. Gott and Weiss (1972) termed these "nibbles," because they were produced by rapid beakoscillations, not pecks. Third, the mode at about 600 msec was almost totally eliminated.…”
Section: Autoregressivementioning
confidence: 99%
See 1 more Smart Citation